Comparison of metabolic adaptations between endurance‐ and sprint‐trained athletes after an exhaustive exercise in two different calf muscles using a multi‐slice 31P‐MR spectroscopic sequence. (2nd February 2018) - Moll, Kevin; Gussew, Alexander; Nisser, Maria; Derlien, Steffen; Krämer, Martin; Reichenbach, Jürgen R.
Abstract : Measurements of exercise‐induced metabolic changes, such as oxygen consumption, carbon dioxide exhalation or lactate concentration, are important indicators for assessing the current performance level of athletes in training science. With exercise‐limiting metabolic processes occurring in loaded muscles, 31 P‐MRS represents a particularly powerful modality to identify and analyze corresponding training‐induced alterations. Against this background, the current study aimed to analyze metabolic adaptations after an exhaustive exercise in two calf muscles ( m. soleus – SOL – and m. gastrocnemius medialis – GM ) of sprinters and endurance athletes by using localized dynamic 31 P‐MRS. In addition, the respiratory parameters VO2 and VCO2, as well as blood lactate concentrations, were monitored simultaneously to assess the effects of local metabolic adjustments in the loaded muscles on global physiological parameters. Besides noting obvious differences between the SOL and the GM muscles, we were also able to identify distinct physiological strategies in dealing with the exhaustive exercise by recruiting two athlete groups with opposing metabolic profiles. Endurance athletes tended to use the aerobic pathway in the metabolism of glucose, whereas sprinters produced a significantly higher peak concentration of lactate. These global findings go along with locally measured differences, especially in the main performer GM, with sprinters revealing a higher degree of acidification at the end of exercise (pH 6.29 ± 0.20 vs. 6.57 ± 0.21). Endurance athletes were able to partially recover their PCr stores during the exhaustive exercise and seemed to distribute their metabolic activity more consistently over both investigated muscles. In contrast, sprinters mainly stressed Type II muscle fibers, which corresponds more to their training orientation preferring the glycolytic energy supply pathway. In conclusion, we were able to analyze the relation between specific local metabolic processes in loaded muscles and typical global adaptation parameters, conventionally used to monitor the training status of athletes, in two cohorts with different sports orientations. Abstract : The effects of different training strategies were resolved by simultaneous monitoring of load‐induced changes of high‐energy phosphates and pH values in multiple muscle groups revealing heterogeneous metabolic adaptations. In addition these results were linked to global physiological regulations, which are commonly used to monitor the training status of athletes. This allows a comprehensive evaluation of training interventions by supporting gold standard methods of sport science with the knowledge of local changes in muscles.